Odpowiedź :
3(2 - 3x) = x - 4
6 - 9x = x - 4
-9x - x = -4 - 6
-10x = -10 | : (-10)
x = 1
4x + 2x + 5 = -2x + 4x + 25
6x + 5 = 2x + 25
6x - 2x = 25 - 5
4x = 20 | : 4
x = 5
3x - 4 = 5x + 2
3x - 5x = 2 + 4
-2x = 6 | : (-2)
x = -3
2x + 3 = -4x - 3
2x + 4x = -3 - 3
6x = -6 | : 6
x = -1
5(2x + 4) - 2x = 4
10x + 20 - 2x = 4
10x - 2x = 4 - 20
8x = -16 | : 8
x = -2
Cześć!
Odpowiedź:
a) x = 1
b) x = 5
c) x = –3
d) x = –1
e) x = –2
Szczegółowe wyjaśnienie:
a)
[tex]3(2 - 3x) = x - 4 = \\ 6 - 9x = x - 4 \\ - 9x - x = - 4 - 6 \\ - 10x = - 10 | \div - 10 \\ x = 1[/tex]
b)
[tex]4x + 2x + 5 = - 2x + 4x + 25 = \\ 2x + 5 = - 2x + 25 \\ 2x + 2x = 25 - 5 \\ 4x = 20 | \div 4 \\ x = 5[/tex]
c)
3x – 4 = 5x + 2 =
3x – 5x = 2 + 4
– 2x = 6 |: –2
x = –3
d)
[tex]2x + 3 = - 4x - 3 = \\ 2x + 4x = - 3 - 3 \\ 6x = - 6 | \div 6 \\ x = - 1[/tex]
e)
[tex]5(2x + 4) - 2x = 4 \\ 10x + 20 - 2x = 4 \\ 8x + 20 = 4 \\ 8x = 4 - 20 \\ 8x = - 16 | \div 8 \\ x = - 2[/tex]